Frequency of Non Odontogenic Lesions with Formation of Bone or Cartilage in Referral Patients to Mashhad Dental School from Dental School Foundation up to 2010 - Ramin Khazraee; Abdollah Javan; Parviz Mahmoodi; Shadi Saghafi; Reza Zare Mahmoodabadi
Introduction: Lesions with formation of bone and/or cartilage are a group of osseous lesions in the jaws including a group of non-neoplastic lesions as well as benign or malignant neoplasm. A group of these lesions are known as fibro-osseous lesions. The purpose of this study was evaluation of clinical and histopathologic characteristics of non odontogenics lesions of the jaws with formation of bone or cartilage in referral patients to Mashhad dental school during 40 years.Materials & Methods: In this study, a review was made of all the biopsies in the histologic dept, of mashhad dental school between 1970 and 2010. Every patient with diagnosis of non odontognic lesion with formation of bone or cartilage was brought into account. Individual informations including gender, age, and region of the lesion, clinical and histologic findings were noted. These data were defined descriptively and were compared by Chi-Square test.Results: A total of 9991 biopsies were reviewed during this study period. Out of these, 133 cases (%1.33) corresponded to non odontogenic lesions with formation of bone or cartilage.Ossifying fibroma with 37 cases (28%) was the most frequent lesion followed by osteosarcoma with 19 cases (14%). The mean age of the patients was 32.2±17.3 years, with minimum age of 9 years and maximum of 75 yrs. In age distribution between different decades of life, most of the lesions were seen in second decade of life with 36 cases. Most of the patients were females with 79 cases whereas males were 54 cases.Conclusion: This study shows that non odontogenic lesions with formation of bone or cartilage have low frequency compared to other lesions of the jaws. Among studied lesions, ossifying fibroma followed by osteosarcoma were the most frequent lesions. Females were more involved than males and most of the lesions occurred in mandible and in posterior area.